Behavioral Test Scores Could Be Linked to the Protein Expression Values of p62 and GLAST in the Brains of Mice with Neuropsychiatric Disorder-Related Behaviors - Yuka Ikeda; Moeka Nakashima; Sayuri Yoshikawa; Kurumi Taniguchi; Naoko Suga; Satoru Matsuda (Biology)
Neuropsychiatric disorders are a public health concern, in which diagnosis and prognosis may be based on clinical symptoms that might often diverge across individuals. Schizophrenia is a major neuropsychiatric disorder, which may affect millions worldwide. However, the biochemical alterations of this disorder have not been comprehensively distinguished. In addition, there is less confidence in finding specific biomarkers for neuropsychiatric disorders, including schizophrenia, but rather a specific characteristic behavioral pattern. In general, maternal immune activation is considered to be one of the important factors in the development of neuropsychiatric disorders. Here, a mouse model of neuropsychiatric disorders was created, in which poly I:C, sodium dextran sulfate (DSS), and κ-carrageenan (CGN) were utilized for maternal immune activation during the pregnancies of mother mice. Subsequently, we examined the link between biochemical changes in p62 and/or glutamate aspartate transporter (GLAST) in the brains of offspring mice and the alteration in their experimental behavior scores. Furthermore, a therapeutic study was conducted on these neuropsychiatric disorder model mice using butyric acid, piceid, and metformin. It was found that some molecules could effectively improve the behavioral scores of neuropsychiatric model mice. Importantly, significant correlations between certain behavioral scores and p62 protein expression, as well as between the scores and GLAST expression, were recognized. This is the first report of a significant correlation between pathological behaviors and biochemical alterations in neuropsychiatric disorder model animals. This concept could contribute to the development of innovative treatments to at least ameliorate the symptoms of several psychiatric disorders.